Exercise During Pregnancy: What Do OB/GYNs Believe and Practice? A Descriptive Analysis - Rachael K. Nelson; Selina M. Hafner; Alyssa C. Cook; Natalie J. Sterner; Erin L. Butler; Brooke E. Jakiemiec; William A. Saltarelli (Women's Health Reports, 2022)
Introduction: Although regular exercise is recommended during non-complicated pregnancies to promote maternal and fetal/infant health, estimates suggest that only 15% of expectant mothers achieve current exercise recommendations. Although lack of motivation and fear related to potential fetal injury are often cited as reasons for not engaging in regular physical activity/exercise during pregnancy, less is understood about individual attitudes and practice habits of obstetrician and gynecologists (OB/GYNs) regarding exercise recommendations that may influence patient engagement in exercise during pregnancy. Purpose: To describe the attitudes, knowledge, and clinical practice of OB/GYNs regarding exercise during pregnancy. Methods: Surveys were sent via U.S. mail to 950 practicing OB/GYNs identified via publicly available databases. The survey included 11 questions regarding demographic information, exercise physiology knowledge, as well as their attitudes and clinical practice recommendations regarding exercise during pregnancy. Results: One hundred thirty-nine completed surveys were returned (14.6% response rate). Ninety-four percent of physicians surveyed agreed that there are benefits of exercise during pregnancy and/or the benefits of exercise during pregnancy outweigh the risks. Ninety-eight percent of physicians surveyed reported that they (or their medical staff) routinely advise their patients to exercise during pregnancy and 46% reported discussing exercise guidelines related to time, intensity, and type of exercise. Only 13% of physicians surveyed reported taking a semester-long exercise physiology course, yet 27% of physicians surveyed reported developing personalized exercise prescriptions for all (6%) or some (21%) of their patients. Conclusions: Low exercise engagement among expectant mothers does not appear to be due to a lack of guidance or negative views of OB/GYNs regarding exercise during pregnancy.